Export horticulture and labour migration in Kenya: Translocality and transiency in a secondary town. Issue 122 (June 2021) - Kuiper, Gerda; Greiner, Clemens
Highlights: Transient secondary towns emerge at foreign investment sites in the Global South. Labour migrants' translocal agency shapes transient urbanization. Flower and vegetable firms have a varied impact on material and social urban space. Abstract: Based on a study of globalized export horticulture at Lake Naivasha, Kenya, this paper explores urban development at the intersections of foreign capital investments and translocal labour mobility. We argue that patterns of translocality largely track the specific requirements and temporalities of the cut flower and vegetable industries, lending an ephemeral and provisional character to the town of Naivasha and the urban sprawl encompassing it. Drawing on empirical research in Naivasha and literature on urbanization in contexts of export agriculture, we contribute to scholarly debates on the transiency of urban spaces in the Global South by focusing on "secondary towns", or those small- and medium-sized towns that rapidly emerge around foreign investment sites. Our findings suggest that urban transiency, understood as a provisional form of urbanism, is especially pronounced in such secondary towns compared to more consolidated urban areas.